COVID‐19 complications among patients with opioid use disorder: a retrospective cohort study across five major NYC hospital systems. (8th January 2023) - Krawczyk, Noa; Rivera, Bianca D.; Basaraba, Cale; Corbeil, Thomas; Allen, Bennett; Schultebraucks, Katharina; Henry, Brandy F.; Pincus, Harold A.; Levin, Frances R.; Martinez, Diana
Abstract: Background and Aims: Individuals with opioid use disorder (OUD) suffer disproportionately from COVID‐19. To inform clinical management of OUD patients, research is needed to identify characteristics associated with COVID‐19 progression and death among this population. We aimed to investigate the role of OUD and specific comorbidities on COVID‐19 progression among hospitalized OUD patients. Design: Retrospective cohort study of merged electronic health records (EHR) from five large private health systems. Setting: New York City, New York, USA, 2011–21. Participants: Adults with a COVID‐19 encounter and OUD or opioid overdose diagnosis between March 2020 and February 2021. Measurements: Primary exposure included diagnosis of OUD/opioid overdose. Risk factors included age, sex, race/ethnicity and common medical, substance use and psychiatric comorbidities known to be associated with COVID‐19 severity. Outcomes included COVID‐19 hospitalization and subsequent intubation, acute kidney failure, severe sepsis and death. Findings: Of 110 917 COVID‐19+ adults, 1.17% were ever diagnosed with OUD/opioid overdose. OUD patients had higher risk of COVID‐19 hospitalization [adjusted risk ratio (aRR) = 1.40, 95% confidence interval (CI) = 1.33, 1.47], intubation [adjusted odds ratio (aOR) = 2.05, 95% CI = 1.74, 2.42], kidney failure (aRR = 1.51, 95% CI = 1.34, 1.70), sepsis (aRR = 2.30, 95% CI = 1.88, 2.81) and death (aRR = 2.10, 95% CI = 1.84, 2.40). Among hospitalized OUD patients, risks for worse COVID‐19 outcomes included being male; older; of a race/ethnicity other than white, black or Hispanic; and having comorbid chronic kidney disease, diabetes, obesity or cancer. Protective factors included having asthma, hepatitis‐C and chronic pain. Conclusions: Opioid use disorder patients appear to have a substantial risk for COVID‐19‐associated morbidity and mortality, with particular comorbidities and treatments moderating this risk.